ENGLIHS: METHODOLOGICAL TRANSFORMATIONS IN SUFISM FROM THE EARLY MASTERS TO THE MODERN INNOVATORS: THE POETIC PHILOSOPHY OF ABU AL-HASAN AL-SHUSHTARI AS AN EXEMPLAR - Mohammed Abdulkareem Yaseen (دی اسکالر)
This article explores the methodological transformations within Sufism from its early foundations to later innovative phases, using the poetic philosophy of Abu al-Hasan al-Shushtari as a representative example. The study outlines historical developments, clarifies linguistic and terminological origins, and identifies the key figures and core themes of early and modern Sufism. Employing a descriptive and historical-analytical approach, it distinguishes between classical Sufism, characterized by strict adherence to Islamic doctrine and ethical discipline, and later forms that incorporated symbolic language and controversial metaphors, often leading to doctrinal debates and criticisms from orthodox scholars. Specifically, the poetry of al-Shushtari is critically analyzed to illustrate how certain symbolic and metaphorical expressions, although artistically influential, have sparked theological controversy due to their potential deviation from established doctrinal and ethical boundaries. The article underscores the necessity of maintaining a careful balance between appreciating the literary contributions of Sufi poets and adhering strictly to Islamic doctrinal principles. Finally, it recommends further scholarly research grounded in methodological rigor and doctrinal clarity, supported by a comprehensive bibliography.